ChemInform Abstract: Electrocatalytic Oxidation of n‐Propanol to Produce Propionic Acid Using an Electrocatalytic Membrane Reactor. Issue 37 (22nd August 2013) - Li, Jiao; Li, Jianxin; Wang, Hong; Cheng, Bowen; He, Benqiao; Yan, Feng; Yang, Yang; Guo, Wenshan; Ngo, Huu Hao
Abstract An electrocatalytic membrane reactor assembled using a nano‐MnO2 loading microporous Ti membrane as an anode and a tubular stainless steel as a cathode is used to oxidize PrOH to produce propionic acid.